Prevalence and determinants of tobacco use among young people in the Gambia - Jallow, Isatou K.; Britton, John; Langley, Tessa (BMJ Publishing, 2017)
Introduction: Tobacco consumption, and consequent morbidity and mortality, are expected to grow most markedly over coming decades in low and middle income countries (LMICs). Preventing tobacco experimentation and uptake among young people in LMICs is therefore vital. However, data on smoking in these countries, particularly in sub-Saharan Africa, remain sparse.